Dynamic Responses of Riparian Vegetation and Macroinvertebrates to Riverine Ecosystems in Dhurchhu and Choekhorchhu, Bumthang (Bhutan Journal of Research and Development, 2026)
A bioassessment study using macroinvertebrates and physicochemical parameters was conducted in Bumthang to compare water quality between Dhurchhu and Choekhorchhu. Systematic random sampling was used to place plots at 150 meters (m) intervals along rivers, and macroinvertebrates were collected using the kick-net method, then counted and identified. Water quality parameters were measured in the field and laboratory and compared with WHO Standards, Ambient Water Quality Criteria, and Bhutan’s Drinking Water Quality Standards. A total of 2,272 macroinvertebrates from 24 families, 9 orders, and one water mite genus were recorded. Plecoptera (n = 1,158) was dominant, while Anisopzygoptera (n = 13) was least abundant. Run habitats had the highest abundance (n = 827) and cascade the lowest (n = 243). Kruskal–Wallis tests showed no significant differences among habitats in Dhurchhu (H(3) = 1.96, p > 0.05) and Choekhorchhu (H(3) = 2.99, p > 0.05). HKHbios and EPT indices indicated good water quality, associated with dominant forest cover (3,271.14 ha) within a 200 m riparian buffer. Increasing sampling points, field verification, and performing seasonal assessments are recommended to determine the effects of vegetation on water quality and macroinvertebrate diversity.
Keywords: EPT; HKHbios; LULC; Macroinvertebrates; Physio-chemical parameters